Problem of evil and Indian thought - "Herman, Arthur L." (Delhi, 1976)
Beginning with the problem of evil in the west, professor A.L. Herman traces the history of one of the most fascinating of all perennial philosophical puzzles. The author identifies some twenty one historical solutions to the problem which are then reduced to eight quite distinct solutions. Prof. Herman then turns in the second part of the book to the history of the problem of evil in Indianthought. The author then joins the analysis of the problem of evil (taken from the first part of the book) to the Indian doctrine of rebirth in order to attempt a solution to the problem. By careful analysis the author shows that the doctrine of rebirth can satisfy the conditions already set forth as adequate for a solution to the problem of evil.
Keywords: Evil